O assujeitamento no discurso proverbial - Oliveira, Maria de Lourdes (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2019)
The purpose of this paper is to discuss the notion of subjection and to analyse the role of the historical and social factors reflected on the subjection of speakers to the proverbial discourse. Its theoretical foundation is discourse analysis of French trend and the corpus is made up of four universes: proverbs from western cultures, eastern and biblical proverbs and proverbs from the Cabinda people. Their pre-constructed assumptions (grossly their enunciations) are imposed in varing degrees upon those who re-anunciate them due, to some extent, to its formal making and, partly , to its formal making and, party, to its ’history’;the institutional determinations of which they habe been the target interfere with the different images the speaking subjects have of the proverb itself and of the universal Subject (cf. Pêcheux). As a consequence, their relationship with both the proverb and the interlocutors themselves is marked by varying subjection/subjetivity levels, and that means this is nort an absolute question, but a relative one.